Determinação de cobre em solos, fungicidas e material vegetal - Brune, Walter; Carlos Gomes , José; Ribeiro , Antônio Carlos (Revista Ceres, 2025)
This paper deals with a microanalytical adaptation to the technique developed by CHENG and BRAY (3) for copper analysis. The adaptation was developed and tested on soils, fungicides and bean seeds as well as on vegetative parts of the bean plant.